Digital tools for knowledge construction in the elementary grades - Blocher, Michael (Rowman & Littlefield, a wholly owned subsidiary of The Rowman & Littlefield Publishing Group, Inc., 2016)
Digital Tools for Knowledge Construction in the Elementary Grades was written for teachers who wish to gain a better understanding of how to integrate technology into their classrooms from a student-centered perspective. When done so, students must take more control of, and therefore more responsibility for, their learning.